In support of the supporters? : Do social forces shape decisions of the impartial? - Thomas J. Dohmen (Institute for the Study of Labor (IZA), 2003)
Analyzing the neutrality of referees during nine German premier league (1. Bundesliga) soccer seasons, this paper documents evidence that social forces influence agents' preferences and decisions. Those, who are appointed to be impartial, tend to favor the home team as they systematically award more injury time in close matches when the home team is behind. Further evidence for similar home bias comes from referees' wrong, or at least disputable, decisions to award goals and penalty shots. The severity of social pressure, measured by the crowd's composition and proximity to the action, determines its effect. Not all agents are affected by social pressure to the same degree.
Keywords: J00; M50; 330; favoritism; principal-agent relationship; personnel economics; Fußballsport; Schiedsgerichtsbarkeit; Soziale Beziehungen; Agency Theory; Deutschland